Using archetypal analysis to derive a typology of knowledge networks in European bioclusters - Milad Abbasiharofteh; Frans Hermans (Regional Studies, 2025)
The shift to a bioeconomy necessitates radical innovations to move from a fossil- to a bio-based economy, with bioclusters playing a crucial role by fostering collaboration among a wide range of co-located actors to find solutions. Through a novel methodological approach in regional studies (i.e., archetypal analysis), this study discusses the specificities of bioclusters and analyses the relational properties within European bioclusters' knowledge networks. Results suggest four archetypal knowledge networks. It is rare to observe the transition of biocluster networks from one archetype group to another. The findings provide a data-driven bioclusters typology, offering insights into designing informed place-based policies.
Keywords: D85; O30; O31; Q57; 330; bioclusters; knowledge networks; inventive activities; archetypal analysis; unsupervised learning